Therapeutic itinerary of patients with chronic low-back pain attending outpatient physiotherapy clinic - Chidozie Emmanuel Mbada; Samuel Olaniyi Oladapo; Chizoba Favour Igwe; Olufemi Oyeleye Oyewole; Clara Fatoye; Abiola Oladele Ogundele; Francis Fatoye (Universidade Federal do Ceará, 2022)
Objective: to assess therapeutic itinerary of patients with chronic low-back pain. Methods: qualitative study involving the use of an in-depth semi structured interviews were used to collect data on therapeutic itinerary among ten patients with chronic low-back pain who from physiotherapy clinic of a tertiary hospital. Data was analysed using thematic content analysis. Results: emerging themes were as follows: onset of low-back pain, symptoms that initiated the journey for care, steps taken to find pain relief, respondent's perception on care received, interference of chronic low-back pain with normal life, family and relations, multiple practices in which chronic low-back pain patients are involved, perception of effectiveness of the multiple practices, and hurdles to seeking care. Conclusion: patients with chronic low-back pain take different routes in search of care. Chronic low-back pain markedly altered patients' life and made them prone to practicing medical pluralism.